Implementation of Career Development Strategies in Improving HR Performance: Case Study in the Indonesian Manufacturing Industry - Carda P, Muhammad; Hasyim (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to analyze the effect of career development strategy implementation in improving the performance of human resources (HR) in the Indonesian manufacturing industry. This study uses a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM) method and SmartPLS 3 application for data analysis. The research sample consisted of 100 respondents. The results showed that the research instrument had excellent internal consistency with a Cronbach's Alpha value of 1,000. The collinearity test indicates that all variables are free from multicollinearity problems with a Variance Inflation Factor (VIF) value of 1,000. R-square analysis showed that the independent variables in this study were able to explain 52.2% of the variation in HR performance, while 47.8% of the variation was explained by other factors not included in this study.However, the influence of career development strategies, job satisfaction, and employee competencies on HR performance was found to be insignificant. Organizational culture has a positive influence on career development strategies but is not significant in improving HR performance. In addition, low work motivation resulted in the influence of career development strategies on employee performance being insignificant. Further research is needed to identify other factors that affect HR performance in the manufacturing industry.